2019
DOI: 10.1002/mds.27727
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation for functional tremor: A randomized, double‐blind, controlled study

Abstract: Objectives The objective of this study was to compare the effect on functional tremor of active versus sham repetitive transcranial magnetic stimulation and investigate whether the addition of hypnosis might help to prolong any repetitive transcranial magnetic stimulation–induced therapeutic effect. Methods We compared the effect of 5 consecutive daily sessions of active/sham repetitive transcranial magnetic stimulation on functional tremor, at 1 and 2 months, in a randomized, double‐blind, 2‐arm, parallel‐con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 45 publications
0
46
0
1
Order By: Relevance
“…This effect still existed 12 months after the start of the invention. A relevant effect of hypnosis could not be shown [31] (HR).…”
Section: Functional Brain Imaging (Spect)mentioning
confidence: 89%
“…This effect still existed 12 months after the start of the invention. A relevant effect of hypnosis could not be shown [31] (HR).…”
Section: Functional Brain Imaging (Spect)mentioning
confidence: 89%
“… 11–15 However, few of these RCTs reported gains in other important outcomes (eg, comorbid psychological/physical symptoms, quality of life/global functioning, healthcare resource use). Despite post-treatment improvements in core FND symptoms following rTMS to M1, Taib et al , 14 for example, did not observe superior improvements in health-related quality of life (SF-36 vitality/general health) for active rTMS relative to sham-TMS, and no improvements were observed in psychological symptoms. Similarly, McWhirter et al 15 reported improvements in subjective symptoms immediately following spTMS of M1 relative to standard care, but no associated improvements in self-reported mental or physical health (SF-12) or clinician-rated disability (Modified Rankin Scale).…”
Section: Introductionmentioning
confidence: 95%
“…In the field of FMD, the use of rTMS as a therapeutic tool is still in its infancy. The published literature includes case report series and a small number of sham-controlled trials, characterized by a substantial variability in design and stimulation parameters (1619). Importantly, these studies evaluated rTMS effects on clinical and behavioral outcomes of FMD, while it is unknown whether rTMS induces neuromodulatory and neuroplastic changes in relevant brain networks, which may underlie the observed clinical effects.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of FMD, the use of rTMS as a therapeutic tool is still in its infancy. The published literature includes case report series and a small number of sham-controlled trials, characterized by a substantial variability in design and stimulation parameters (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%